International Pissouri Village Symposium: Media and Democracy - Pleios, George; Violakis, Petros; Kampaki, Maria Christina; Letsiou, Roxanthi; Aspriadis, Neofytos; Yadav, Sudarshan; Zubok, Yulia; Chankova, Elena; Voskarides, Sotos; Alkiviadou, Natalie (My University, 2020)
Media plays a critical a role today for the protection and the strengthening of peaceful democratic societies. On the other hand, Democracy gives us freedom—’the right to free speech’. The media through television channels, the Internet, and newspapers assume the role of the moral guardian in society. More than often, we depend on the media to seek the truth. But truth is subjective. What is truth to you might not be the truth to me. Therefore, the media is expected to carefully analyze a situation from all possible angles rather than merely pass a fixed moral judgment. This International Symposium today we discuss with the question of the role of mass media in modern democracies. Mass communication is indispensable for today’s large-scale societies, and television, newspapers and the radio are the most important sources of information for citizens all around the globe. But while there seems to be great consensus about what this means for dictatorships and countries in transition, the contribution of mass media to the wellfunctioning of more mature and established democracies is highly debated among scholars, politicians and practitioners alike. There is usually no doubt that mass media help maintaining the system and the power of the government in authoritarian regimes where they are – at least for the most part – tightly controlled by the state.
Keywords: Media; Democracy; Mass media; Mass communication